Chitosan/carboxymethyl cellulose wound dressings supplemented with biologically synthesized silver nanoparticles from the ligninolytic fungus Anamorphous Bjerkandera sp. R1 (2022)
ABSTRACT: Chitosan (CHI) and carboxymethyl cellulose (CMC) are naturally sourced materials with excellent physical, chemical, and biological properties, which make them a promising tool for the development of different medical devices. In this research, CHI-CMC wound dressings were manufactured, by using different colloidal suspensions of silver nanoparticles (AgNPs) synthesized from the ligninolytic fungus Anamorphous Bjerkandera sp. R1, called CS and SN. Transmission electron microscopy (TEM), UV-Vis spectroscopy, and dynamic light scattering (DLS) analysis were used to characterize AgNPs. The wound dressings were characterized, by scanning electron mi- croscopy (SEM), optical microscopy and their mechanical, antimicrobial, and biological properties were evaluated. The results of the different characterizations revealed the formation of spherical AgNPs with a mean size between 10 and 70 nm for the different mixtures worked. The mechanical properties of CHI-CMS-AgNPs doped with CS and SN suspensions showed superior mechanical properties with respect to CHI-CMC wound dressings. Compared to the latter, CHI-CMC-AgNPs wound dressings yielded better antibacterial activity against the pathogen Escherichia coli. In biological assays, it was observed that manufactured CHI-CMC-AgNPs wound dressings were not toxic when in contact with human skin fibroblasts (Detroit). This study, then, suggests that this type of wound dressings with a chitosan matrix and carboxymethyl cellulose doped with biologically synthesized nanoparticles from the fungus Bjerkandera sp., may be an ideal alternative for the manufacture of new wound dressings.